2011
DOI: 10.1007/s10450-011-9370-2
|View full text |Cite
|
Sign up to set email alerts
|

FTIR studies of butane, toluene and nitric oxide adsorption on Ag exchanged NaMordenite

Abstract: In this work, we studied the adsorption of butane, toluene and nitric oxide on NaMordenite exchanged with different amounts of silver. The reactions that occurred when the adsorbed hydrocarbons interacted with NO and the effect of water adsorption were also addressed. Different silver species were formed after ion exchange and they were detected by TPR analysis. Highly dispersed Ag 2 O particles were reduced at temperatures lower than 300°C whereas Ag + exchanged ions showed two TPR peaks, which can be ascribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 32 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…Previous studies also reported that high temperatures up to 1173 K were required to reduce the Ag in AgZ crystals. The AgZ used in these studies was prepared by ion exchange of commercial NaZ (Si/Al: 6.5:1) in AgNO 3 solution, which had different properties to the commercial AgZ pellets (Si/Al: 5:1) used in this study.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies also reported that high temperatures up to 1173 K were required to reduce the Ag in AgZ crystals. The AgZ used in these studies was prepared by ion exchange of commercial NaZ (Si/Al: 6.5:1) in AgNO 3 solution, which had different properties to the commercial AgZ pellets (Si/Al: 5:1) used in this study.…”
Section: Resultsmentioning
confidence: 95%
“…This could indicate that a higher fraction of oxide is present in this sample or that the oxide clusters are slightly larger than those in Ag 10 M. The TPR results 26,27 shows that a higher silver content increases the amount of oxide formed in the sample volume. An important advantage of this technique is that it is element specific, thus providing selective information on silver.…”
Section: Extended X-ray Absorption Fine Structure (Exafs)mentioning
confidence: 84%
“…The first of them can be attributed to the reduction of Ag2O present in extra-framework positions. Two reduction peaks with the maximum at higher temperature may be assigned to reduction of silver species (Ag + ions) at exchange positions and/or strongly interacting with zeolite support (probably two types of silver species) [45].…”
Section: Temperatureprogrammed Reduction Resultsmentioning
confidence: 99%